The impact of a female international field hockey tournament on performance and markers of immune status and muscle damage - Macutkiewicz, D.; Sunderland, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Background: International field hockey tournaments requires teams to play a series of matches on consecutive days with no more than 1-2 days recovery before the next match. Little is known about the performance and physiological impact of such a schedule on elite female players. In male international field hockey players alterations in motion characteristics and the intermittent nature of the activity are altered with repeated match exposure (Sunderland et al., 2008). The aim of the present study was to assess the impact of a tournament schedule on performance, markers of immune status and muscle damage of elite female hockey players. Method: Ten female international field hockey players gave informed consent to participate in the study. The mean (SD) age and mass of the players were 25.2 (4.0) years and 64.4 (6.4) kg respectively. Data were collected during a 5 day tournament (non ranking) period comprising: day 1-2, and 4-5 match days and day 3 recovery day. Fasted capillary blood samples were taken on all days. Plasma samples were analysed for immunoglobulin A (IgA), Creatine Kinase (CK), C-reactive protein (CRP) and Urea. Unstimulated saliva samples were taken for all days and analysed for testosterone, cortisol and testosterone/cortisol ratio (T/C ratio). A global positioning system was used to assess distance covered at particular speeds (`standing` 0-0.7; `walking` 0.7-6.1; `jogging` 6.1-11.2; `running` 11.2-15.1; `fast running` 15.1-19.1; `sprinting` >19.1 km/h), intensities (`low` 0-6.1; `moderate` 6.1-15.1; `high` >15.1 km/h) and heart rate. Data was analysed using 1- and 2-way ANOVA with repeated measures. Statistical Significance was set at P<0.05. Results: No differences were observed in the mean distance covered between games 1-4. As the tournament progressed no significant differences were observed in the distances covered in motion type or intensity. IgA was significantly lower on day 3 (1.46 (0.6) g/l, P=0.018) when compared to day 4, which corresponded to two consecutive matches (Day 1 and2) and a recovery day on day 3. CK increased from 116.0 (28.8) U/l at rest to 165.9 (42.8) U/l (P=0.026) after the second game, reduced below initial baseline following a recovery day and subsequently increased after the following game (181.7 (77.1) U/l; P<0.001). Conclusions: The repeated match play experienced in the present tournament did not result in any residual or accumulated fatigue. It is possible that a more demanding competitive schedule such as that experienced during the Olympic Games will have an effect of the activity patterns of players during later matches.